TIG Torch melting as surface engineering technology - Azwan, Muhammad; Maleque, Md. Abdul; Rahman, Mohammad Mustafizur (Elsevier, 2020)
This paper aims to review and emphasis on the benefit and development of tungsten inert gas (TIG) torch surface melting as surface engineering technology. The melting approach in surface engineering was highlighted which include surfacing methods such as powder blown or injection, wire feed and powder preplacement method. The attractive features of TIG torch surfacing method are emphasized. Numerous research works are reviewed on the application of TIG torch surface melting technology for surface modification of different types of metallic materials. The effect of processing parameters of TIG torch surface melting technology is emphasized and it can be seen that the heat input and welding speed are the most significant parameters. The paper also presents a success story to further strengthen the potential application of TIG torch surface melting technique on surface engineering technology.